Comparative study of off-grid and grid-connected hybrid power system: issues, future prospects and policy framework - Bankole Adebanji; Oluwaseun Atoki; Taiwo Fasina; Oluwumi Adetan; Adewale Abe (Institute of Advanced Engineering and Science, 2021)
A sustainable energy system is of utmost importance for any significant development in any nation.This work identified some obstacles inhibiting rapid renewable energy growth in Nigeria and recommended some policy measures in overcoming them. Moreover, a comparative study of off-grid (OG) and grid-connected (GC) small hydro-solar photovoltaic-diesel hybrid system was carried out using Oyan river, Abeokuta, Nigeria as a case study. The hybrid components were modeled with and without the grid. The hydro solar resources data of the area were collected and analyzed using hybrid optimization model for electric renewable (HOMER) software. The simulation results proved that the GC hybrid power system is better than the OG hybrid power system in technical and economic terms depending on the location. This paper, therefore, proposed the use of OG hybrid power system for electrification of distant villages especially where extending the grid seems infeasible and the use of GC hybrid power system in the urban areas. The work will assist power sector stakeholders in making informed decisions towards the growth of hybrid power system technology in Nigeria.